Peran desain web, kualitas informasi, layanan pengiriman dalam peningkatan kepuasan elektronik dan niat beli kembali produk Sociolla - Kamila, Adinda Cahya; Ilfitriah, Aniek Maschudah (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
The purpose of this research is to examine the role of Web Design, Information Quality, Delivery Service on Electronic Satisfaction and the influence of Electronic Satisfaction on Sociolla customers Repurchase Intentions. The population in this research are users of the Sociolla application or website throughout Indonesia. This research used a sampling technique in the form of purposive sampling with 159 respondens who had made at least two purchases via the Sociolla application or website as a samples. The data was analyzed using the SEM-PLS technique and processed using the SmartPLS 4 program. The reults obtained in this research show that Web Design, Information Quality, and Delivery Service as a whole have a significant positive effect on Electronic Satisfaction. In addition, Electronic Satisfaction has a significant positive effect on Repurchase Intention of customers using the Sociolla application or website.